Introduction - Pereira, Alfredo [UNESP]; Pickering, William Alfred; Gudwin, Ricardo Ribeiro (Taylor & Francis, 2018)
This introduction presents an overview of the key concepts of discussed in the subsequent chapters of this book. The book describes foundational concepts. It focuses on biophysical and cognitive approaches to Self-Organization, complex dynamics of living systems, self-organized adaptation, and learning in computational systems. The book discusses practical issues of information technology and related ethical questions, all dealt with in the social context of community Self-Organization and technology. It also describes a semiotic perspective, investigating the convergence of Charles Sanders Peirce philosophy with the study of Self-Organization, an original pathway of research contributing to a dialogue between pragmatism, semeiotics, complexity theory, and self-organizing systems. The dynamics of self-organizing systems is heavily dependent on the information that is available to and processed by their sub-systems. A self-organizing system is conceived as an open system that builds its organization and functionality from the patterns of interaction of its components.